Spatially resolved in vivo plant metabolomics by laser ablation-based mass spectrometry imaging (MSI) techniques: LDI-MSI and LAESI - Bartels, Benjamin; Svatoš, Aleš (Frontiers in Plant Science, 2015)
This short review aims to summarize the current developments and applications of mass spectrometry-based methods for in situ profiling and imaging of plants with minimal or no sample pre-treatment or manipulation. Infrared-laser ablation electrospray ionization and UV-laser desorption/ionization methods are reviewed. The underlying mechanisms of the ionization techniques–namely, laser ablation of biological samples and electrospray ionization–as well as variations of the LAESI ion source for specific targets of interest are described.